Heat Transfer and Entropy Generation on Free Convection Airflow inside a T-shaped Cavity Considering Inner Obstacles (Jagannath University Journal of Science, 2024)
In this study, a numerical analysis of heat and entropy generation on free convection of airflow is performed inside a T-shaped cavity with and without circular obstacles. The T-shaped cavity is formed with two symmetrically isothermal rectangular blocks. A cold temperature is maintained on the cavity's upper wall. The adiabatic walls are connected to heated wall at constant temperature. It is assumed that the flow is laminar, 2-D, and steadily incompressible. The finite element analysis is employed for solving the governing equations. The calculated results are compared and validated with the other published works. The dimensionless velocity (streamlines) and temperature (isotherms) are calculated and illustrated for varying Rayleigh numbers. It is found that the average Nusselt number at the heated walls and entropy generation inside the cavity increase with the increment of Rayleigh numbers. Moreover, the thermal performance effects on natural convection flow are investigated with circular obstacles inside the enclosure. Five cases without and with circular obstacles regarding the boundary conditions are investigated. It is found that the thermal performance of the cavity can be improved by adding two circular obstacles with cool boundary conditions. It is evident that the innovative structure by adding two circular obstacles with cool boundary conditions gives higher average Nusselt number and entropy generation whereas lower Bejan numbers for varying Rayleigh numbers. The study is performed for  and .Jagannath University Journal of Science, Volume 11, Number 1, June 2024, pp. 186−202